2021
DOI: 10.2147/dddt.s341271
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacokinetics/Pharmacodynamics of Fixed-Dose Combination of Esomeprazole and Calcium Carbonate (AD-206) to the Conventional Esomeprazole

Abstract: Purpose: Proton pump inhibitors (PPIs) are used for the treatment of acid-related disorders. Demands for enhanced stability and faster onset led to the development of AD-206, a fixeddose combination of a PPI (esomeprazole) with an antacid salt (calcium carbonate). This study compared the pharmacokinetics (PKs) and pharmacodynamics (PDs) of AD-206 (Addpharma) with conventional esomeprazole (Nexium ® , AstraZeneca). Materials and Methods:A randomized, open-label, two-treatment, two-sequence crossover study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…)1( . Esomeprazole (ESO) is a proton pump inhibitor (PPI) (1) because it inhibits gastric acid secretion (3,2) ., including Zollinger-Ellison syndrome, as well as the treatment and prevention of gastric and duodenal ulcers and erosive esophagitis (4,5) and also works to eliminate stomach germs (helicobacter pylori) and heartburn (6) .…”
Section: Introductionmentioning
confidence: 99%
“…)1( . Esomeprazole (ESO) is a proton pump inhibitor (PPI) (1) because it inhibits gastric acid secretion (3,2) ., including Zollinger-Ellison syndrome, as well as the treatment and prevention of gastric and duodenal ulcers and erosive esophagitis (4,5) and also works to eliminate stomach germs (helicobacter pylori) and heartburn (6) .…”
Section: Introductionmentioning
confidence: 99%
“…5 Acid control for GERD patients improved considerably after the novel PPI esomeprazole was introduced to the market in 2001 in the United States and major European countries. 6 It has been confirmed that the food effect influences the pharmacokinetics of esomeprazole due to variability in stomach emptying and stimulation by bile flow, which causes changes in drug metabolism, and physical or chemical drug interactions. The pharmacodynamic (PD) effect of esomeprazole, including inhibition of gastric acid secretion and increase in the duration of time with intragastric pH > 4.0, correlates with the area under the concentration-time curve (AUC).…”
mentioning
confidence: 99%
“…5 They covalently bind with the H + , K + -ATPase enzyme and irreversibly inactivate the proton pump. 5,6 Esomeprazole, as the S-enantiomer of omeprazole and the first single optical isomer in the PPI family, 7 is widely used for GERD. Furthermore, esomeprazole has a good pharmacokinetic (PK) profile in the gastrointestinal tract 8 as its peak plasma concentration (C max ) may be attained within 1-2 hours after oral administration with higher and more consistent bioavailability than omeprazole.…”
mentioning
confidence: 99%
See 2 more Smart Citations